Functional leaf traits and biodiversity effects on litter decomposition in a stream - Markus H. Schindler; Mark O. Gessner (Ecology, 2009)
Rapid loss of biodiversity worldwide has raised concerns about the consequences to ecosystem functioning, including processes such as litter decomposition. Consequent experiments with litter mixtures to assess effects of changing tree composition and diversity on decomposition have given mixed results, but the causes are not clear. Reasoning that such conflicting accounts reported in the literature may be reconciled by considering differences in functional litter traits, we conducted a field experiment in a stream with leaf litter from nine deciduous tree species mixed in a total of 40 combinations. Fine‐mesh and coarse‐mesh litter bags were used to distinguish between potential effects mediated by microbial decomposers and detritivores. We hypothesized that diversity effects would emerge in species mixtures containing functionally dissimilar leaves but be absent in mixtures of functionally similar litter as assessed by determining proximate lignin, nitrogen, and phosphorus contents of the litter. Mean decomposition rates of litter mixtures did not lend support to our hypothesis for either microbial decomposition (as inferred from mass loss in fine‐mesh litter bags) or decomposition caused by both microbes and detritivores (mass loss from coarse‐mesh bags). Decomposition rates were largely controlled by litter lignin content, whereas P and especially N were not important. In line with our hypothesis, the most recalcitrant (slowly decomposing) and most labile (rapidly decomposing) species decomposed slower and faster, respectively, in litter mixtures comprising different decay categories than in homogenous mixtures composed of a single decay category or in single‐species litter bags. However, across decay categories, evidence was weak in support of the idea that functional litter dissimilarity matters, in spite of plausible mechanisms that could cause such effects.